Systematic omics analysis identifies CCR6 as a therapeutic target to overcome cancer resistance to EGFR inhibitors - Eun-Ji Kwon; Hyuk-Jin Cha; Haeseung Lee (iScience, 2024)
Summary: Epidermal growth factor receptor inhibitors (EGFRi) have exhibited promising clinical outcomes in the treatment of various cancers. However, their widespread application has been limited by low patient eligibility and the emergence of resistance. Leveraging a multi-omics approach (>1000 cancer cell lines), we explored molecular signatures linked to EGFRi responsiveness and found that expression signatures involved in the estrogen response could recapitulate cancer cell dependency on EGFR, a phenomenon not solely attributable to EGFR-activating mutations. By correlating genome-wide function screening data with EGFRi responses, we identified chemokine receptor 6 (CCR6) as a potential druggable target to mitigate EGFRi resistance. In isogenic cell models, pharmacological inhibition of CCR6 effectively reversed acquired EGFRi resistance, disrupting mitochondrial oxidative phosphorylation, a cellular process commonly associated with therapy resistance. Our data-driven strategy unveils drug-response biomarkers and therapeutic targets for resistance, thus potentially expanding EGFRi applicability and efficacy.